Comparative study of self-compassion and sense of coherence in nurses of psychiatric hospitals - Nosratabadi Iman; Ameri Golnaz Forough; Iranmanesh Sedigheh; Asadi Neda (Sciendo, 2023)
Nurses, due to the nature of their job, are subjected to various forms of stress and physical and psychological injuries. Self-compassion and a sense of coherence have attracted much attention in research in recent years as having high potential for improving the health and performance of people in the workplace. The present study aimed to compare self-compassion and the sense of coherence in nurses working in psychiatric hospitals and other hospitals of Kerman University of Medical Sciences.